Pulmonary arterial hypertension associated with systemic sclerosis. (April 2011) - Mathai, Stephen C; Hassoun, Paul M
Systemic sclerosis (SSc) is commonly complicated by pulmonary arterial hypertension (PAH), which is a leading cause of death in the SSc patient population. Owing to the fact that the risk of developing pulmonary hypertension is high, screening is important, although the optimal modality remains to be defined. Furthermore, despite recent advances in therapy for PAH, the response to these interventions in patients with PAH with SSc has been discouraging. The lack of clinical response to these therapies may merely reflect the limitations of traditionally employed PAH outcome measures in SSc-PAH patients or highlight the heterogeneity of the disease manifestations within SSc. Importantly, since extrapulmonary involvement of the GI tract and kidneys by SSc limit candidacy for lung transplantation, new therapies that target abnormal cellular proliferation in the pulmonary vasculature are currently under investigation and may be particularly relevant to SSc-PAH.